KEMAMPUAN SISWA MENGIDENTIFIKASI KARAKTER TOKOH DALAM CUPLIKAN NOVEL REMAJA YANG DIBACAKAN KELAS VIII.2 SMPN 19 PEKANBARU KECAMATAN RUMBAI PESISIR: (Student's Ability to Identify Characters in Snippets of Young Adult Novels that are Read by Class VIII.2 SMP 19 Pekanbaru Kecamatan Rumbai Pesisir) - Nazirun Nazirun; Karsinem Karsinem; Siti Albaniah (UIR Press, 2015)
The ability to hear is to hear something in earnest: the ear to hear good to hear. Problems examined: 1) What is the student's ability to identify characters in teen read snippets novel class of SMPN 19 Pekanbaru VIII.2 Kecamatan Rumbai Pesisir to log the main characters and side characters? 2) How the student's ability to identify characters in snippets of young adult novels that are read class VIII.2 SMP 19 Pekanbaru Kecamatan Rumbai Pesisir identifying figure main characters and figures on the side?. This research aims: 1) To obtain the student's ability to identify characters in teen read snippets novel class of SMPN 19 Pekanbaru VIII.2 Kecamatan Rumbai Pesisir to log the main characters and side characters in the novel footage remaja.2) To obtain the student's ability to identify the character in snippets young adult novels that are read class VIII.2 SMP 19 Pekanbaru Kecamatan Rumbai Pesisir identifying figure main characters and figures sideline. The theory that I use in this study theory Aminuddin, Nurgiyantoro, and Suharma. The sample consists of one class, namely the overall total of 36 grade students VIII.2. This research uses descriptive method. This study using observation and tests. The hypothesis of this study are: 1) The ability of students to identify characters in snippets of young adult novels that are read class VIII.2 SMP 19 Pekanbaru Kecamatan Rumbai Pesisir to log the main character and the character sideline in snippet novel read categorized enough (50-69). 2) The ability of students to identify characters in snippets of young adult novels that are read class VIII.2 SMP 19 Pekanbaru District of Rumbai Coastal identifying figure main characters and character sideline on the novel read categorized enough (50-69). Thus, the ability of the average, students in grades VIII.2 SMPN 19 Pekanbaru record the main character, byproduct, and the main characters and side scored 82.54 categorized both on the range of values (70-89), then the hypothesis that the ability grade students VIII.2 SMPN 19 Pekanbaru Kecamatan Rumbai Pesisir to log the main character, byproduct, and identify which character protagonist and sideline Uncategorised reasonably rejected